1999
DOI: 10.1017/s0012162299000110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating research in developmental disabilities: a conceptual framework for reviewing treatment outcomes

Abstract: The study of developmental disabilities, not being confined to one medical field, poses a challenge in evaluating outcomes research. It is a multidisciplinary area of study which encompasses health-care, rehabilitation, psychosocial, educational, and biotechnology specialties and involves biological, social, and behavioral effects of intervention. Consequently, there is a lack of consistency in what has been studied, how the outcomes have been measured, and where these results have been recorded. Naturally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 8 publications
0
43
0
1
Order By: Relevance
“…29 In that model, shifts in 'impairment' were assumed to be precursors to changes in 'disability' (activity) that then became forerunners to changes in 'handicap' (participation). One can also consider the possibility of reverse or multidirectional influences in which changes in activity or participation might influence body functions and structures or a different area of activity, 32 as illustrated by the ICF model. When the predictor list for GMFM change was expanded to a higher outcome level to include PEDI FS mobility and PODCI global change scores in the regression analysis, the regression models changed, although no additional variation was explained (illustrated in Scenario 2, Appendix I).…”
Section: Discussionmentioning
confidence: 99%
“…29 In that model, shifts in 'impairment' were assumed to be precursors to changes in 'disability' (activity) that then became forerunners to changes in 'handicap' (participation). One can also consider the possibility of reverse or multidirectional influences in which changes in activity or participation might influence body functions and structures or a different area of activity, 32 as illustrated by the ICF model. When the predictor list for GMFM change was expanded to a higher outcome level to include PEDI FS mobility and PODCI global change scores in the regression analysis, the regression models changed, although no additional variation was explained (illustrated in Scenario 2, Appendix I).…”
Section: Discussionmentioning
confidence: 99%
“…Specific studies on the efficacy of intervention on the outcome of children with brain injury are few, mostly due to the difficulty in conducting such studies and in diagnosing brain injury (Butler et al, 1999). Only five such studies are found in the literature.…”
Section: Newborn Brain Injury; Stimulation; Intervention; Outcomementioning
confidence: 99%
“…Fazzi et al, 1997;Norr et al, 2003;Parker, Zahr, Cole, & Brecht, 1992;Schuler, Nair, & Kettinger, 2003;Zigler & Muenchow, 1992). Therefore, a rich environment with intensive stimulation may well allow infants with brain injury to recover.Specific studies on the efficacy of intervention on the outcome of children with brain injury are few, mostly due to the difficulty in conducting such studies and in diagnosing brain injury (Butler et al, 1999). Only five such studies are found in the literature.…”
mentioning
confidence: 99%
“…To determine the value of the evidence available about an intervention, we applied Sackett's method for grading research (Sackett 1989) with minor modifications supported by research of the American Academy for Cerebral Palsy and Developmental Medicine (Butler et al 1999, Butler andDarrah 2001). Table III provides an overview of Sackett's levels of evidence for grading research.…”
Section: Methodsmentioning
confidence: 99%
“…The review of Vermeer and Bakx (1990) was chosen as a reference base for practical and methodological reasons: we had access to the database and notes that were made during (Sackett 1989) modified by Butler et al (1999) and Butler and Darrah (2001); see also Table III. -, unspecified; +limited; ++, detailed. Pre, non-randomized trial without control participants.…”
Section: Methodsmentioning
confidence: 99%